Organic food purchase habits in Hungary - Szente, Viktória; Torma, Dorisz (Journal of Economic Development, Environment and People, 2015)
In Hungary organic food market has both demand and supply oriented aspect: several times not necessary products are distributed while the selection and volume of certain products are not satisfactory. Thus our aim was to develop a coordinated benchmark strategy to increase the trade of organic products. To get more details about the Hungarian organic food market we applied the “mystery shopping” method to observe changes in organic food supply and carried out a quantitative survey using a 1,000 member countrywide panel. Our results indicate that organic origin is considered somewhat important for every 4th respondent, while only 3.7% of the interviewees paid attention to put organic food products into their cart. The most serious obstacle is the doubt of surveyed individuals about the authenticity and the alleged benefits of organic products, complete with a high perceived price. “Price” is the most influential factor on shopping decision, but the advantageous “constant quality” and “health benefit” factors are just following it. Most of the respondents stated that they buy organic products directly from the producer (27.4%), but small retail outlets are likewise popular (though to a somewhat lesser extent). In conclusion, there is potential demand for ecological food products in Hungary. Although the proportion of conscious consumers is small; it significantly exceeds the current market share of the products. Consumers should be approached with better prices, smart retailing solutions and through awareness raising.